Influence of temperature and exercise on growth performance, muscle, and adipose tissue in pacus (Piaractus mesopotamicus) - dos Santos, Vander Bruno; de Oliveira, Marcelo Wendeborn Miranda; Salomão, Rondinelle Artur Simões [UNESP]; Santos, Rosemeire de Souza; de Paula, Tassiana Gutierrez [UNESP]; Silva, Maeli Dal Pai [UNESP]; Mareco, Edson Assunção (Elsevier, 2017)
The aim of this study was to evaluate the effects of temperature and swimming exercise on fish growth in pacus (Piaractus mesopotamicus). Pacus weighing 0.9 – 1.9 g and 2.7 – 4.2 cm in standard length were cultivated at an initial density of 120 fish m−3 in 3 recirculation systems containing 6 water tanks at a volume of 0.5 m3 each at temperatures of 24, 28 and 32 °C. At each temperature, three tanks were modified to generate exercise activity in the specimens and force the fish to swim under a current speed of 27.5 cm s−1. At the end of the experiment, the following metrics were evaluated: fish performance, morphometry (length, width, height and perimeter in different body positions), and the diameter and density of muscle and subcutaneous ventral adipose tissues. At 28 °C, pacus were both heavier and had greater weight gain after 240 days of cultivation. Additionally, exercise improved the feed conversion. An increase of 4 °C (30 °C) did not provide any improvement in the performance of the fish. However, swimming exercise improved the performance of pacus, providing increases of 38% and a 15% improvement in feed conversion. Both temperature and exercise influenced the body morphology (especially in the caudal region) and the cellularity of white and red muscle fibers and adipocytes.
Keywords: Adipocyte; Feed conversion; Hypertrophy; Morphology; Muscle fibers; Water flow